2016
DOI: 10.1111/sji.12414
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyreactivity Confers a Holistic Role in the Immune System

Abstract: In this review, we summarize and discuss some key findings from the study of naturally occurring autoantibodies. The B-cell compartment of the immune system appears to recognize almost all endogenous and environmental antigens. This ability is accomplished principally through autopolyreactive humoral and cellular immune receptors. This extended autopolyreactivity (1) along immunoglobulin gene recombination contributes to the immune system's ability to recognize a very large number of self and non-self constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 100 publications
3
13
0
Order By: Relevance
“…Such antibodies may have biological effects on autologous "target" cells that may be necessary for their homeostatis. 45 Finally, interpretation of these in vitro data is in agreement with the current lack of evidence of anti-Neu5Gc Abs-induced vascular inflammation in vivo in humans, and particularly when a very strong exposure to elicited anti-Neu5Gc Abs was documented for several months, 7 and in whom no vascular toxicity was reported. 15,46 Furthermore, aggressive experimental conditions aimed at inducing a xenosialitis condition in the human-like Cmah-KO mice did not result in noticeable vascular inflammation at the clinical and histological levels, although inflammatory markers were found in circulation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Such antibodies may have biological effects on autologous "target" cells that may be necessary for their homeostatis. 45 Finally, interpretation of these in vitro data is in agreement with the current lack of evidence of anti-Neu5Gc Abs-induced vascular inflammation in vivo in humans, and particularly when a very strong exposure to elicited anti-Neu5Gc Abs was documented for several months, 7 and in whom no vascular toxicity was reported. 15,46 Furthermore, aggressive experimental conditions aimed at inducing a xenosialitis condition in the human-like Cmah-KO mice did not result in noticeable vascular inflammation at the clinical and histological levels, although inflammatory markers were found in circulation.…”
Section: Discussionsupporting
confidence: 79%
“…To some extent, anti‐Neu5Gc Abs may thus behave as other “natural antibodies” found in all normal human sera, which react against a variety of autologous antigens. Such antibodies may have biological effects on autologous “target” cells that may be necessary for their homeostatis …”
Section: Discussionmentioning
confidence: 99%
“…I did neither find (circumstantial) evidence that these specialized NAb-producing B cells exist in chickens, nor find evidence that these B cells do not exist in chickens. This is in line with one of the current ideas that the NAb-producing B cells are too diverse to characterize (Tumas-Brundage et al, 2001;Avrameas, 2016). Actually I hypothesize that NAb producing B cells might not exist at all (in chicken).…”
Section: Literature Citedsupporting
confidence: 84%
“…Originally, NAb in mice and humans were thought to be solely produced by one subpopulation of B cells: the B1 B cell. However, new insights have included many new NAb-producing B cell types at different locations, and it is now suggested that "well-defined [NAb]-synthesizing B-cell subsets apparently do not exist, but are rather a continuum of functional and phenotypic B-cells that cannot be clearly defined (Tumas-Brundage et al, 2001)" (cited from Avrameas (2016)). This fits with the absence of success to define the NAb-producing B cell in livestock species (i.e.…”
Section: Box 3: Natural Antibody-producing B Cellsmentioning
confidence: 99%
“…They are typically polyreactive, have low binding affinity, and may recognize a broad spectrum of antigens including non-self and self-antigens (e.g. single-stranded DNA, carbohydrate epitopes) [ 39 , 40 ]. NAAbs primarily belong to the IgM isotype—the most ancient of the antibody classes, also found in sharks in trans-membrane and secretory forms [ 41 , 42 ].…”
Section: The Healthy Aspect Of Self-recognitionmentioning
confidence: 99%